1970
DOI: 10.3329/jafmc.v6i2.7272
|View full text |Cite
|
Sign up to set email alerts
|

Is English as a Medium of Instruction Problem for Undergraduate Medical Students?

Abstract: Introduction:The students of a country like Bangladesh, where language of medical education is completely English, suffer from a lot of problems in grasping English and also Latin and Greek terms used in English. Objective: This study was aimed to estimate the extents and to identify the nature of the problems faced by the undergraduate students in different aspects of English used in Anatomy. Methods: The study was conducted on 191 third year medical students, who had just passed the Anatomy portion of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Understanding medical terminology was found to be one of the major issues facing a group of Bangladeshi medical students. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding medical terminology was found to be one of the major issues facing a group of Bangladeshi medical students. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…Understanding medical terminology was found to be one of the major issues facing a group of Bangladeshi medical students. [6] It has been suggested that more effort should be made to improve language-learning strategies, rather than the time allocated for learning a language, to ensure better proficiency. The two major aspects to be considered here are: Identification and comparison of the learning strategies used by more and less successful English language learners, and develop instructions for less successful learners that would help them become more successful in their language study.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomy, nervous system, and all other organs learning are some of the beginner and basic subjects in medical colleges in Bangladesh. It is quite a big challenge for any new comer Bengali-based learner to memorize these terminologies as well as their functionality since all the textbooks were written by English speaking background (ESB) writers [17]. This is why we proposed a mobile-AR based application to assist and improve students selflearning skills.…”
Section: Existing Ar Based Mobile/web Application For Anatomy Learmentioning
confidence: 99%
“…so that continued education can be provided without getting much affected during the quarantine period. 6,7,8 Also various eteaching software's are being explored by teachers to bring maximum possible ease for their students. Considering the relatively recent advent of this teaching methodology in India, both teachers and students are still in the process of getting acquainted with the new system.…”
Section: Introductionmentioning
confidence: 99%